Statistical Estimation of Modern Trends and Prospects of the Size and Structure Population of Ukraine - Palian Z. О.; Bondarenko, I. H. (Statistics of Ukraine, 2017)
A balanced change in demographic processes should be considered as a prerequisite and, at the same time, as a result of the stable development of the state. Reproduction intensity depends not only on the character of demographic behavior, but also on the presence of contingents of the population, providing or potentially able to provide for its replacement. The dynamics of Ukrainian population, the transformation of its gender-age structure during the period of independence, taking into account the intensive and structural factors of natural increase and migration, is considered. During 2002-2015, the regime of survival and fertility improved in Ukraine, due to which the depopulation slowed down somewhat. But even these positive changes do not compensate for the loss of population size as a result of systematic aging, reducing the proportion of reproductive contingent and its aging. Significant demographic losses, direct and indirect, were caused by a hybrid war from Russia. Alienation of the territory of the Crimea and parts of Donbas is not only a minus 2.5 million citizens of Ukraine. This is a change in the structure of the population - a decrease in the proportion of older age groups that increase the demographic load and worsen the characteristics of survival and fertility of the maternal generation. In this work are presented the results of the short-term simulation of population size and structure taking into account modern trends of replacements components and existing administrative-territorial changes. Two scenarios of the forecast for 2018 have been developed, and the base year it was taken in 2013, when the Crimea was part of Ukraine. The first, realistic scenario was based on the preservation of the current situation - Ukraine without the annexed Crimea and the occupied part of the Donbas. The second scenario imitates the return to Ukraine of all the lost territories. Simulation showed that the population of Ukraine will be reduced by both scenarios, but to 41.9 million people under the scenario without the occupied and annexed territories and to 44.7 million people in the second scenario. The finish of war will due to slow down the death rate to 14.9%0. The age structure of the population does not differ significantly in two scenarios, because the forecast horizon is very short (4 years). The share of generation of parents and women of reproductive age in both variants of the forecast decreases. However, in the case of returning Crimea, it will be even lower (47.4% vs. 47.5% in the first scenario). The reason for this is the emigration of young and middle-aged people to the mainland of Ukraine and to the Russian Federation, which provided some preferences to the settlers from Ukraine. Expected structural changes combined with the modern life and fertility regime will worsen natural population growth rates in both scenarios. In further research is planned to build trend models of births and deaths that will allow the artificially restore the interrupted time series due to administrative-territorial incomparability of data on demographic events